2013
DOI: 10.1016/j.virol.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of pancreatic cancer cells to oncolytic vesicular stomatitis virus: Role of type I interferon signaling

Abstract: Oncolytic virus (OV) therapy takes advantage of common cancer characteristics, such as defective type I interferon (IFN) signaling, to preferentially infect and kill cancer cells with viruses. Our recent study (Murphy et al., 2012, J. Virol., 86: 3073-87) found human pancreatic ductal adenocarcinoma (PDA) cells were highly heterogeneous in their permissiveness to vesicular stomatitis virus (VSV) and suggested at least some resistant cell lines retained functional type I IFN responses. Here we examine cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
160
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(180 citation statements)
references
References 60 publications
16
160
4
Order By: Relevance
“…VSV is a negative-sense RNA virus that can infect a wide variety of animals and cells and possesses a rapid lytic replication cycle but demonstrates dramatic sensitivity to the host interferon response (16,30,32,33). The high sensitivity of VSV to innate interferon responses and its lack of pathogenicity to humans have made it an attractive oncolytic platform that has been extensively investigated and has been shown to kill cancer cells selectively, particularly when they have a disrupted interferon response (28)(29)(30)(31)(32)(33)(34). Preclinical studies show that VSV is promising for the treatment of a variety of human cancers (10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VSV is a negative-sense RNA virus that can infect a wide variety of animals and cells and possesses a rapid lytic replication cycle but demonstrates dramatic sensitivity to the host interferon response (16,30,32,33). The high sensitivity of VSV to innate interferon responses and its lack of pathogenicity to humans have made it an attractive oncolytic platform that has been extensively investigated and has been shown to kill cancer cells selectively, particularly when they have a disrupted interferon response (28)(29)(30)(31)(32)(33)(34). Preclinical studies show that VSV is promising for the treatment of a variety of human cancers (10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…VSV is a Vesiculovirus of the family Rhabdoviridae with a negative-sense RNA genome (16,17). VSV is a preferred candidate as a platform for oncolytic virus development against a variety of cancers (10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), primarily due to its very broad tropism infecting a wide variety of animals and different cells, its short replication cycle, and high sensitivity to host interferon-mediated antiviral activity (28)(29)(30)(31)(32)(33)(34)(35). Tumor-selective tropism can be further enhanced by mutating the M protein or engineering the virus to encode beta interferon (IFN-␤).…”
mentioning
confidence: 99%
“…Our recent study analyzed several VSV recombinants in an array of human PDA cell lines in vitro (23,24) and in xenografts in athymic mice (24). These studies demonstrated excellent abilities of VSV recombinants to infect and kill a majority of tested human PDAs and revealed that intact type I IFN signaling in some PDAs was responsible for their resistance to OV therapy (23).…”
mentioning
confidence: 99%
“…PCR was carried with the following conditions: reverse transcription at 50 C for 30 min, denaturation at 94 C for 15 min followed by 35 cycles of denaturation at 94 C for 45 s, annealing at 57 C for 45 s, extension at 72 C for 45 s before a final elongation step at 72 C for 8 min. All the primers used for the PCR were previously published and designed to amplify cellular mRNAs by Moerdyk-Schauwecker et al (2012). PCR products were electrophoresed on a 1 % agarose gel with GelRed nucleic acid stain (Biotium) and pictures acquired using Gel Doc EZ Imager (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…However, so far PDA cells have displayed mixed susceptibility to OVs (Lee et al, 2014;Moerdyk-Schauwecker et al, 2012;Murphy et al, 2012;Wennier et al, 2011), underscoring that virotherapy for tumours which tend to be heterogeneous in nature should not rely on a short list of possible candidates.…”
Section: Introductionmentioning
confidence: 99%